PENGARUH PROPERTI PERTAMBANGAN DAN PERPUTARAN PERSEDIAAN TERHADAP KINERJA KEUANGAN - Jihan Rafifah Wijaya; Reza Benny Zafira; Patricia Keizi Prabandari (Nindikayla Institute, 2023)
The purpose of this study is to find the effect of mining properties and inventory turnover on financial performance. This study uses quantitative methodology using Return On Equity (ROE) and Return On Investment (ROI) to represent firm performance. The data source on this study from annual reports and financial reports on the Indonesia Stock Exchange (IDX). This study examined 35 samples of mining companies sector for the 2015-2021 period with data processing using SPSS software to analyze multiple linear regression. There is 2 result in this study. The result are tested mining property as independent variable has no effect on Financial Performance, and the other independent variable which is Inventory Turnover has an effet on Financial performance. This research only concludes 35 data, based on 6 mining companies from 2015 to 2021. This research is expected to be able to share an explanation for shareholders and companies to determine the variables that affect financial performance, especially the mining sector companies. Mining property and inventory turnovers that simultaneous tested for significant result on financial performance are so slight in the past. And also, company's samples from 2015 to 2021 are the newest study data for this research